Wife’s Obligations According to Marriage Law: Perspective of Legal Purpose Theory - Hidayat, Deden Adi; Nurcholis, Moch (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. The wife’s obligations under marriage law are contrary to Islamic law.. This difference raises questions about the suitability of the law with social values. Social history records significant developments in the role of the wife in the dynamics of household affairs. Aims. To analyze the basis of Article 34 paragraph 2 of the Marriage Law concerning the wife's obligation to manage household affairs and theoretical views on the purpose of the law on the article. Methods. Normative legal research uses a conceptual approach to explore the understanding of the basis of law. Data were obtained through literature studies and analyzed descriptively based on the theory of the purpose of law. Results. Article 34 paragraph 2 iin terms of justice, reflects distributive and commutative justice. The fair division of roles between husband and wife is reflected and affirms equality in lineage and family identity. Justice will be achieved by avoiding exploitation or inequality in the exchange of roles. The wife's obligations in terms of benefits are considered an effort to achieve the greatest possible benefits for individuals and families. Consistent and clear application of the law is very important in terms of certainty. The history of marriage law shows the complexity in the interpretation and application of the law. Efforts to create legal certainty have been made through the unification and simplification of laws, as well as the affirmation of norms that regulate the wife's obligations firmly and unambiguously.